Evaluasi Kebijakan Kawasan Tanpa Rokok di Rumah Sakit Umum Haji Surabaya - Rahma, Nuzulia; Yulianti, Tri; Sukristyanto, Agus (Universitas 17 Agustus 1945 Surabaya, 2018)
The objective of this research is to evaluate the implementation policy of Surabaya government related to non-smoking area In accordance with the Mayor of Surabaya Regulation No. 25 of 2009 on the Implementation of Local Regulation of Surabaya City Number 5 Year 2008 About Non Smoking Area at RSU Haji. This research used qualitative descriptive using three informants comprises two visitors of RSU Haji and one staff of RSU Haji. The technique of data collections used in this research is observation, interview, and documentation. The results of this study explain that the evaluation of the policy as a functional activity conducted by the researcher states that the functional implementation of the Surabaya City government policy related to non-smoking areas at the RSU Haji functionally has succeeded. Evaluations focused on policy have also been undertaken by the researcher and he/she found that the implementation of the smoking policy in RSU Haji area has been implemented inaccordance with the provisions. As well as, systematic policy evaluation conducted by the researcher stated that the policy has been running in accordance with provisions and running without any obstacles.Keywords: public policy, policy evaluation, RSU Haji, No-Smoking area